Pengaruh Citra Perusahaan Dan Reputasi Terhadap Kualitas Pelayanan Dan Dampaknya Pada Kepuasan Pelanggan (Pada Nasabah Tabungan Bank Artha Graha) - Mukti Rahardjo, Kevin dan (Jurnal Manajemen Bisnis dan Kewirausahaan, 2019)
This study aims to analyze the influence of corporate image and reputation on service quality and its impact on customer satisfaction in PT. Bank Artha Graha Tbk. This research used quantitative methods. The data is the primary data obtained through the distribution of questionnaires. The population in this study was customers of Bank Artha Graha, Tbk. The number of samples was determined by using Hair et.al. (1998) sampling method that is at least 5 times the number of parameters used in the study. The number of sample collected was 215 respondents. Using multiple linear regression analysis, it was found that corporate image and company reputation to have direct and significant positive effect on service quality and customer satisfaction on Bank Tabungan Graha Bank Tabungan Graha. Corporate image and company reputation has contributed 77.1% to the quality of service. In addition, the quality of service has direct and significant positive impact on service satisfaction on the Bank Tabungan Graha Bank Tabungan Graha. Contribution of company influence, company reputation and service quality equal to 71,5% to customer satisfaction. Corporate image has indirectly affected customer satisfaction through service quality at Bank Artha Graha Tbk that is 5,5% similarly, Company Reputation has indirectly influence to customer satisfaction through service quality at Bank Artha Graha Tbk that is equal to 5,3%. To improve customer satisfaction the company must maintain the corporate image abd reputation of the company through the quality of service.